(untitled) (Fiep Bulletin - online, 2011)
Introduction: The school lunch is an important meal of public school students in Brazil, this situation is worsened in the poorest regions of Brazil and the Amazon region, because in many cases is the only daily meal for the student; studies that actualize the assessment nutritional status are of great value, highlighting the importance of a balanced diet to be offered in public school lunches in Brazil. Objective: To evaluate the nutritional status of students from 7-10 years of public schools in Marabá. Methods: The study was conducted with 2505 students from 13 public schools in Marabá, in 5 cities (New Address-MN, SF-San Feliz, NM-New Marabá, Marabá Pioneer-MP, New City, NC). The children were evaluated by classifying Wateelow (1977). Data analysis was performed using the Epi Info 6.0 and Program Assessment and Nutritional Status in Pediatrics (PED, 2000). Results and Discussion: The nutritional profile to be established was the Great Obese-GO, OB, Obese, Overweight-SP, Eutrophic-EU, Malnourished now-DA stunted Malnourished-DP, chronic malnourished-DC. GO was not detected in MN, SF and MP, with only incidence of 0.24%, 0.31% and NM-CN. OB were observed: 0.15%-MN, SF-0.12%, 1.32%-NM, MP-0.47% and 2.08%-CN. SP: NM-0.04%, 0.28%-SF-NM 1.72%, 0.44%-MP and 2%-CN. U.S.: found 2.08%-MN, 1.8%-SF-NM 13.17%, 4.55%, and 16.45% MP-CN. DA:% 1-MN, 1.32%-SF-NM 7.98%, 4.11%-MP and 11.1%-CN. SD: 0.52%-MN, 0.84%-SF-NM 6.35%, 2.48%-MP and 8.1%-CN. DC: 0.24%-MN, 0.4%-SF-NM 2.87%, 1.92%, 3.55% MP and-CN. Conclusion: Eating habits are inadequate, observing a low intake of food of nutritional value and low consumption of vegetables, fruits and vegetables, and these habits must be changed to not cause future complications, whereas 52.2% of students are in groups of malnutrition (DA, DP, DC), before this fact is important to emphasize the public policies on education and health related to correct nutrition.